Characterization of copy number variants for CCL3L1 gene in rheumatoid arthritis for French trio families and Tunisian cases and controls. Issue 8 (August 2016) - Ben Kilani, Mohamed; Achour, Yosser; Perea, Javier; Cornelis, François; Bardin, Thomas; Chaudru, Valérie; Maalej, Abdellatif; Petit-Teixeira, Elisabeth
Abstract Analyses of copy number variants (CNVs) for candidate genes in complex diseases are currently a promising research field. CNVs of C–C chemokine ligand 3-like 1 (CCL3L1 ) gene are candidate genomic factors in rheumatoid arthritis (RA). We investigatedCCL3L1 CNVs association with a case-control study in Tunisians and a transmission analysis in French trio families. Relative copy number (rCN) ofCCL3L1 gene was quantified by droplet digital PCR (ddPCR) in 100 French trio families (RA patients and their two parents) and in 166 RA cases and 102 healthy controls from Tunisia. We calculated odds ratio (OR) to investigate association risk forCCL3L1 CNVs in RA. rCN identified varied from 0 to 4 in the French population and from 0 to 7 in the Tunisian population. A significant difference was observed in the distribution of these rCNs between the two populations (p = 2.34 × 10−10 ), as when rCN from French and Tunisian RA patients were compared (p = 2.83 × 10−5 ). CNVs transmission in French RA trios allowed the characterization of genotypes with the presence of tandem duplication and triplication on the same chromosome. RA association tests highlighted a protective effect of rCN = 5 forCCL3L1 gene in the Tunisian population (OR = 0.056; CI 95 % [0.01–0.46]). Characterization of CCL3L1 CNVs with ddPCR methodology highlighted specific CN genotypes in a French family sample. A copy number polymorphism of a RA candidate gene was quantified, and its significant association with RA was revealed in a Tunisian sample.